2017
DOI: 10.1039/c6cc09184a
|View full text |Cite
|
Sign up to set email alerts
|

Diacenaphthylene-fused benzo[1,2-b:4,5-b′]dithiophenes: polycyclic heteroacenes containing full-carbon five-membered aromatic rings

Abstract: We herein report on an efficient synthesis of diacenaphthylene-fused benzo[1,2-b:4,5-b']dithiophenes and demonstrate that their packing structure in the solid state depends on the substituent groups. These compounds form dimers with their radical cations in high concentration solution and exhibit good field-effect mobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…A There is the usual monoclinic herringbone motif between layers (Figure 8). 31 (C 8 −O), the alkoxy chains adopted a similar conformation to compounds 3a−d with a step from the oxygen to the first methylene group, C1′, and a gauche conformation about the C1′−C2′ bond (Figure 9). However, two examples 10 EGOKIW 29 and 11 XURLUT 30 (both C 12 −O) (Figure 10) displayed different side chain arrangements from their close analogues 7 and 8.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A There is the usual monoclinic herringbone motif between layers (Figure 8). 31 (C 8 −O), the alkoxy chains adopted a similar conformation to compounds 3a−d with a step from the oxygen to the first methylene group, C1′, and a gauche conformation about the C1′−C2′ bond (Figure 9). However, two examples 10 EGOKIW 29 and 11 XURLUT 30 (both C 12 −O) (Figure 10) displayed different side chain arrangements from their close analogues 7 and 8.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…Five examples containing a central benzo­[1,2- b :4,5- b ]­dithiophene core, and carrying two alkoxy groups at the opposing central 4,8-positions, were found. In three of these 7 EGOFAJ (C 8 –O), 8 XURLON (C 12 –O), and 9 UCIVOU (C 8 –O), the alkoxy chains adopted a similar conformation to compounds 3a – d with a step from the oxygen to the first methylene group, C1′, and a gauche conformation about the C1′–C2′ bond (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, Li, Hartl, and Yang et al reported optimized conditions for a palladium-catalyzed C–H activation reaction of benzo[ b ]thiophene with 1,8-dibromonaphthalene, which gave the acenaphthylene product 264.1 in 69% yield ( Scheme 264 ). 496 By applying this protocol, it was also possible to react fused dithiophenes with 1,8-dibromonaphthalene in a 1:2 ratio, to obtain compounds 264.2a – c and 264.3 in 26–90% yield. Additionally, the para -benzoquinone 264.3 could successfully be converted to the diyne 264.2d in 22%.…”
Section: Nonbenzenoid Fusionmentioning
confidence: 99%
“…Synthesis and derivatization of fluoranthenes have received much attention in the recent years. Diels–Alder reaction and transition metal-catalyzed reactions are the most commonly used methods for their synthesis. …”
Section: Introductionmentioning
confidence: 99%